(untitled) (Lafia Journal of Scientific and Industrial Research, 2025)
The opening of the Benue Trough as well as the sinistral displacement of the strike slip fault that displaced the whole inlier has been well documented in recent times. Fractures formed are believed to have occurred at the time of the opening of Benue Trough in the Cretaceous. Large sedimentary basins were developed with carbonates and continental platforms that provided ideal conditions for the formation of suits of sandstone hosted, stratiform deposits such as barite, celestine and fluorite of Cretaceous age. Barite is the economic mineral and the shape of the ore bodies is considered massive, the gangue minerals are calcite, traces of celestine and silica. A fluid inclusion and stable isotope analysis (S and O) for barite was conducted. The result shows a melting ice temperature between −24 °C and −15 °C (salinities of 13.6 to 24 wt. % NaCl equiv.) and a homogenization temperature ranged between 60 °C to 155 °C. Isotopic analysis of barite showed δ34SVCDT ranges from +18.1‰ to +19.8‰. Sulfur and Oxygen isotope data for the barite from the study area is consistent with a sulfur source formed during the Cretaceous, which coincides with the age of the Bima Formation. The oxygen isotope analysis showed a range between δ18OVSMOW 9.9‰ and 12.2‰ for the mineral. Fluid inclusion microthermometry and isotopic measurements lead us to conclude that brines from the Upper Benue Basin led to the replacement of evaporite strata (gypsum) by barite and its subsequent deposition within veins and fractures of the Bima Formation.